Degradation of chloramphenicol by α-FeOOH-activated two different double-oxidant systems with hydroxylamine assistance. (July 2020) - He, Fu; Ma, Wencheng; Zhong, Dan; Yuan, Yixing
Abstract: The pipe deposits from water distribution network are iron-wastes, which could be used as a catalyst of advanced oxidation processes (AOPs). This paper prepared one main composition (α-FeOOH) of pipe deposits and compared the difference of chloramphenicol (CAP) degradation by α-FeOOH-activated hydrogen peroxide/persulfate and α-FeOOH-activated hydrogen peroxide/peroxymonosulfate with hydroxylamine assistance. Several key affecting factors were investigated. The results revealed that the double-oxidant system has a synergy effect in CAP degradation process. The hydroxyl radicals were identified as the predominant radicals in two different degradation processes via electron paramagnetic resonance (EPR) technique. The possible degradation pathways and products were confirmed by liquid chromatography-mass spectrometry (LC-MS). This study provided a theoretic research for pollutant removal by taking full advantage of pipe deposits and advance the development of water quality security in water distribution network in future. Graphical abstract: Image 1 Highlights: The main composition of pipe deposits of water distribution network, α-FeOOH, was prepared. Compared CAP removal difference in two double-oxidant degradation systems. The OH was the predominant active species. Degradation products of CAP were identified by LC-MS.